AN EXAMINATION OF WORK FROM HOME AND WORK - FAMILY LIFE BALANCE INTERACTION IN THE CONTEXT OF BURNOUT DURING COVID-19 PANDEMIC - TURHAN, Işıl; DEMİRBİLEK, Sevda (SSD Journal, 2022)
The pandemic size of Covid-19 in a short time, necessitated new regulations in almost every area of social life. With the massive shift to work from home, employees have had to carry out their work responsibilities and home responsibilities in the same physical environment. With the opportunities provided by information and communication technologies, employees are accessible around the clock by their employers, colleagues or business partners who need to be in contact with each other. Working from home, along with the benefits, provides to employees, can also cause work-family life balance problems and burnout problem depending on the increased permeability between home and work lives. Personal variables such as the gender of the employee, having children and the age range of the children also affect the work-family life balance problem and the level of burnout. The aim of the study is to determine the effect of the compulsory work from home, which is carried out by the teachers working within the Ministry of National Education during the Covid-19 epidemic, on the work-family life balance and the existence of the burnout problem experienced in this context. The study also makes it possible to make a comparison between teachers working in public and private schools in terms of work-family life balance problems and burnout. In the study, descriptive research method was used. The data were collected by conducting in-depth interviews with 20 teachers working in public and private schools affiliated to the Ministry of National Education in the Marmara Region and selected using the criterion sampling method. The data obtained were analyzed in the MAXQDA qualitative data analysis program and six main themes were revealed. These themes are; the effects of family life on the phenomenon of working from home, the effects of working from home on family life, the need for support and support mechanisms, The advantages and disadvantages of the home working system, views on working conditions in private/public schools, and teachers’ views on the education system. According to the results of the research, in summary, teachers working in private schools experience more intense work-family life balance problems and burnout than their colleagues working in public schools during the work from home process. The underlying reasons for this situation can be explained by the factors such as the expectation of a more intense work pace and the lack of job security.